EFFECT OF SACCHAROMYCES CEREVISIAE ON THE CHARACTERISTICS OF RUMEN FLUID AND SOME OF BLOOD VARIABLES IN ADULT AWASSI LAMLS - Shihab, O. H.; Al-jumaily, M. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate the effects of adding different concentrations of yeast on some of rumen fluid traits and some blood characteristics in adult Awassi lambs. The study was conducted in the animal house at the College of Veterinary Medicine/University of Tikrit for the period from 15/7/2017 to 1/10/2017, using 16 Awassi lambs, aged (10 – 12 months), and an average weight of (36 kg)., The animals were divided into four groups, each one included four lambs. The first group was considered as control (T1), without the addition of bread yeast to their foods. The diets in the other groups, (T2), (T3) and (T4) contained the yeast in the proportions of 3, 5 and 7 gm/ animal / days, respectively. Wheat straw was introduced as a free coarse feed as well as concentrated feed at 2.5% of weight, which is measured weekly for 75 days. The study showed no significant differences in the concentration of ammonia, volatile fatty acids and pH, measured after 1 and 3 hours with feed. While the pH was significant (P≤0.05) immediately after feeding, no significant differences were found in all studied blood characteristics except, which are the levels of cholesterol and total protein ,which was differ significantly (P≤0.05) .